Intestinal parasites of the grey fox (Pseudalopex culpaeus) in the central Peruvian Andes - Moro P.L. (1998)
This study was funded in part by NIH grant no.U01A135894-01 and funds by CONCYTEC, Lima, Peru.The authors thank J.D. Moro, N. Perez-Palma, J.B. Phu, D.Sara, Amanda Chavez and Eva Casas for editorial help.We also thank Armando Gonzales, Cesar Gavidia, NestorFalcon for helpful comments and M. Gamarra and R.Zarate from Tupac Amaru for their cooperation.